Opportunities and challenges in the analysis of the Multilingual Assessment Instrument for Narratives (MAIN). Issue 2 (April 2022) - De Cat, Cécile
The development of the Multilingual Assessment Instrument for Narratives (MAIN) has no doubt contributed to prompting a renewed interest in children's narratives. This carefully controlled test of narrative abilities elicits a rich set of measures spanning multiple linguistic domains and their interaction, including lexis, morphosyntax, discourse-pragmatics, as well as various aspects of narrative structure, communicative competence, and language use (such as code-switching). It is particularly well suited to the study of discourse cohesion, referential adequacy and informativeness, and of course to the study of narrative structure and richness, and the acquisition of a more formal or literary register. In this commentary article, I reflect on the five empirical papers included in the special issue. I focus on methodological challenges for the analysis of narratives and identify outstanding questions.